AN ANALYSIS OF FACTORS AFFECTING CIRCULAR MIGRATION INTEREST OF RESIDENTS IN NEGARA SUB-DISTRICT OF JEMBRANA REGENCY OF BALI PROVINCE - Anifatul Hanim; Sudaryanto -; Ida Wahyuni; Ivana RD (UPT Penerbitan Universitas Jember)
Imbalance of economic development between city to cities in Indonesia creates unequal economic development especially in human migration.This research attempts to find out the factor that influence of human migration among cities. The commuter theory behind the research has being used as the based point to evaluate the significant level of influencing factors. Population on the research is the community of Negara Sub-district of Jembrana Regency Denpasar Bali. Cluster random sampling was used to develop profile of respondents both commuter and non-commuter residence. Logistic Regression Analysis. Some variables, such as age, income, education, and marital status to the circular migration interest are employed. The result of logistic regression model of analysis confirmed that the variable of age, income, education, and marital status has affected significantly to the circular migration interest of the residents in Negara Sub-district of Jembrana Regency. Overall logistic regression model used in this research could confirm the factors affecting the respondents’ interest to perform circular migration. It showed thatthe respondents’ behavior in this research was likely to have an interest of migration due to their desire to improve their family quality of life.